2022
DOI: 10.1108/apjba-09-2021-0480
|View full text |Cite
|
Sign up to set email alerts
|

Linking entrepreneurial competencies, innovation and sustainable performance of manufacturing SMEs

Abstract: PurposeThe purpose of this study is twofold: to examine the impact of entrepreneurial competencies and innovation on manufacturing small and medium-sized enterprises' (SMEs) sustainable performance and to explore the role of innovation as a mediator on the relationship between entrepreneurial competencies and manufacturing SMEs' sustainable performance.Design/methodology/approachData collected from manufacturing SMEs in Malaysia were analysed via the partial least squares-structural equation modelling (PLS-SEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 85 publications
2
16
0
Order By: Relevance
“…ECs were assessed using 14 measures from Man et al (2008) that evaluated opportunity, strategic and conceptual abilities. Many prior investigations, for example (Al Mamun et al, 2019;Al Koliby et al, 2022a;Aftab et al, 2022), have been empirically confirmed. Similarly, KM was assessed using 12 items from Al Koliby et al (2022b) that evaluate knowledge acquisition, dissemination and application.…”
Section: Questionnaire Development and Instrumentmentioning
confidence: 77%
See 3 more Smart Citations
“…ECs were assessed using 14 measures from Man et al (2008) that evaluated opportunity, strategic and conceptual abilities. Many prior investigations, for example (Al Mamun et al, 2019;Al Koliby et al, 2022a;Aftab et al, 2022), have been empirically confirmed. Similarly, KM was assessed using 12 items from Al Koliby et al (2022b) that evaluate knowledge acquisition, dissemination and application.…”
Section: Questionnaire Development and Instrumentmentioning
confidence: 77%
“…Hence, it is imperative for organizations to possess the requisite competencies to foster growth and progress (Al Mamun et al, 2018). Certainly, it is evident that managers and proprietors of manufacturing SMEs possessing robust ECs prioritize long-term performance objectives, emphasizing factors such as environmental sustainability, community well-being and public safety, as highlighted by Al Koliby et al (2022a). The empirical findings indicated that ECs are a notable predictor SP (Seraj et al, 2022).…”
Section: Entrepreneurial Competency and Sustainable Performancementioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, environmental dynamism reinforces the beneficial association between ECs and performance [22]. The findings of [23] acknowledged that ECs played vital roles in fostering SMEs' innovation and long-term success. Additionally, innovation partially moderated the relationship between ECs and manufacturing SMEs' sustainable performance.…”
Section: Entrepreneurial Competencies (Ecs)mentioning
confidence: 84%